Effectiveness of hyperbaric oxygen therapy in irradiated maxillofacial dental implant patients: A systematic review with meta-analysis - Darshana Nilesh Shah; Chirag Jasubhai Chauhan; Jenish Sureshbhai Solanki (Wolters Kluwer Medknow Publications, 2017)
The significantly higher implant failure rates in maxillofacial patients, undergoing radiotherapy, might be caused by the long-term effects of reduced vascularization compromising the implantation site. An extensive preclinical animal literature and a multitude of clinical reports suggest the use of hyperbaric oxygen (HBO) therapy as it can improve the tissue vascularity. Hence, it may increase the implant survival rate by enhancing osseointegration process in such patients. The objective of this systematic review was to investigate the effectiveness of HBO therapy on dental implant survival rate in irradiated maxillofacial patients who require prosthodontic rehabilitation. An electronic search without time restrictions was undertaken in April 2016 using databases: PubMed, Google Scholar, and the Cochrane Oral Health Group Trials Register. We also tried to contact the manufacturers and researchers in the field for necessary details. Clinical human studies, on irradiated maxillofacial dental implant patients, including randomized controlled trials (RCTs), prospective controlled trials, retrospective studies, and preliminary reports were included in the study. Data collection was carried out by two of the authors' independently. The titles and abstracts of all reports were screened for the study design and type of reported intervention; all the duplicates were removed. The data search yielded 62 titles, out of which 14 articles were selected for the study by the article filtration criteria: Title/abstract/full text. Data which were extracted by two authors with any disagreement were resolved by the third author, and a meta-analysis was done using binary random-effect model. The results show decreased implant failure rate in HBO group (9.21%) compared to non-HBO group (22.44%). The potential limitations of this study are amount of radiation doses used, period lasting from radiotherapy to the placement of the implants, and follow-up period which varies for every subject of the included study, which can affect the treatment outcome. Although there are many sensitive articles published about HBO, including a number of review papers, RCTs are still lacking. According to the statistical analysis, it can be concluded that preventive HBO therapy can reduce the risk of implant failures in irradiated patients by 1.21 (relative risk) with 95% confidence interval (P < 0.001). Hence, HBO can be the effective treatment protocol for the implant treatment in irradiated maxillofacial patients.